Determination of the impact on the use of bio-inputs in agricultural production in the department of Boyacá - Lara Castro , Sergio Andrés
Sustainable agriculture for several years has been gaining strength, since its purpose is to harmonize agricultural production with care for the environment and conservation of natural resources, by reducing the use of chemical substances in production processes. According to official data, 42% of the main fertilizer (Urea) consumed in Colombian agriculture comes from Ukraine and Russia. On the other hand, the risks and dangers that arise when using chemical products not only have a high negative impact on nature, but in the same or worse way on the health of the farmer and his product, a study carried out at the end of 2011 in Colombia reveals that for every 100,000 inhabitants there were 4,835 deaths due to poisoning thanks to pesticides of chemical origin. This research work makes known to Interest Groups such as farmer associations, agro-industrial educational institutions, Technologies and faculties related to agriculture, the impact it has on the environment, health and the development of agriculture, in the department of Boyacá, the use of chemicals in farmed soils, in parallel to the use of bio-inputs free of chemical agents, and inform the benefits that friendly alternatives represent, through different means of dissemination, such as flyers among others focused on generating awareness in the population of what is actually being consumed.